2020
DOI: 10.14720/aas.2020.115.1.1258
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic interference of Sonchus oleraceus L. with wheat and the associated weeds: a field study

Abstract: <p>A field study was conducted to examine the allelopathic potential of Sonchus oleraceus L. residue against the weeds associated with wheat crop. Residue application was carried out under field conditions in two doses: 150 and 300 g m−2. Weed richness, density and above-ground biomass were assessed at 6 and 12 weeks after application to evaluate the potential effect of S. oleaceus manure on weed control. Some growth criteria and the total yield of the cultivated wheat crop were also measured. The residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Hassan et al [38] confirmed that S. oleraceus inhibited germination and growth of Brassica nigra and Melilotus indicus. The results of Hassan [39] suggest that S. oleraceus could affect the productivity of wheat and cause weed suppression due to its allelopathic potential. The aqueous extract of S. oleraceus (8%) can be used for controlling red rice weed [40].…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al [38] confirmed that S. oleraceus inhibited germination and growth of Brassica nigra and Melilotus indicus. The results of Hassan [39] suggest that S. oleraceus could affect the productivity of wheat and cause weed suppression due to its allelopathic potential. The aqueous extract of S. oleraceus (8%) can be used for controlling red rice weed [40].…”
Section: Discussionmentioning
confidence: 99%